CT IMAGING IN THE ELDERLY: ADDRESSING CHALLENGES AND ENHANCING DIAGNOSTIC ACCURACY - Uliana Pidvalna; Ihor Romaniuk; Anna Voitovych; Marianna Mirchuk (Anti-Aging Eastern Europe)
The increasing proportion of elderly individuals globally presents challenges in healthcare. Computed tomography (CT) is a widely utilized radiological modality valued for its rapid acquisition capabilities and accessibility. CT interpretation in elderly patients might be complicated due to age-related physiological changes: decreased bone density, organ elasticity, and increased calcifications. These factors, along with comorbidities like cardiovascular disease, diabetes, and cognitive impairments, complicate CT interpretation. Elderly people are at increased risk of contrast-induced nephropathy due to reduced renal function. Metal fragments, such as pacemakers, coronary stents and stent-grafts, are additional artefacts during CT. Moreover, patient cooperation can be limited by conditions such as dementia or hearing loss, leading to issues with motion and positioning during scans. Considering age-related changes and comorbidities, the solutions in CT scanning might be personalized and specific to the elderly CT protocols. Pre-CT preparation, including clear instructions and strategies for patients with cognitive impairments or physical limitations, is beneficial. Multidisciplinary collaboration among radiologists, geriatricians, and specialists enhances diagnostic accuracy and cooperation. Technological advancements reduce artefacts, enhance image quality, and lower radiation exposure. Educating medical staff on the needs of elderly patients ensures better comfort and care. Implementing complex solutions for optimizing CT imaging might improve the diagnostic outcomes and patient experience.